2009
DOI: 10.1590/s0102-79722009000100012
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento humano e violência de gênero: uma integração bioecológica

Abstract: ResumoO objetivo da presente pesquisa foi compreender a etiologia da violência de gênero usando a Teoria Bioecológica do Desenvolvimento Humano. A abordagem bioecológica concebe a violência de gênero como um fenômeno multidimensional embasado em uma interação de diversos fatores. Assim, neste artigo emprega-se o modelo bioecológico como uma ferramenta heurística para organizar esses fatores em quatro níveis: pessoal, que compreende as características biológicas e psicológicas da pessoa; processual, que envolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
23

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 27 publications
2
14
0
23
Order By: Relevance
“…Thus, even considering that men are the main aggressor in the domestic environment, it is valid to recognize that women can also play the role of perpetrator of abuse, especially in its physical and psychological forms. Some studies have suggested that such events can be triggered by a situation of response by the victim when faced with constant aggressions suffered, which corroborates the need to understand this phenomenon as the generator of cyclical and interdependent suffering (2,9) . For the effective control of this complex phenomenon, it is not enough to characterize the victim, as such a position would be considered partial and focused only on the actors present in these relations.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Thus, even considering that men are the main aggressor in the domestic environment, it is valid to recognize that women can also play the role of perpetrator of abuse, especially in its physical and psychological forms. Some studies have suggested that such events can be triggered by a situation of response by the victim when faced with constant aggressions suffered, which corroborates the need to understand this phenomenon as the generator of cyclical and interdependent suffering (2,9) . For the effective control of this complex phenomenon, it is not enough to characterize the victim, as such a position would be considered partial and focused only on the actors present in these relations.…”
Section: Discussionmentioning
confidence: 71%
“…To broaden the vision beyond the position of a victim also appears to be indispensable to advance the programs to control these phenomena. Some studies have already pointed in this direction, principally by inferring the possibility of losses in the family care process in face of the disregarding of violence as a cyclical and bidirectional entity, and also by the recognition of those who also suffer in these situations: the victim, the perpetrator and all the other actors which comprise the family nucleus (8)(9) . In this sense, a profound reflection on the profile of women involved in situations of violence appears to be ever more necessary, in order to aggregate new perspectives on the existing knowledge.…”
mentioning
confidence: 99%
“…A similar study had already pointed to the risk relations between intimate partner physical abuse and follow-up of children in primary care units, highlighting that care mainly exercised by women themselves can be influenced by their level of autonomy and capacity to mobilize and manage the necessary resources 27 . Studies have shown that the harms caused by a conflictive family environment act in a vicious circle; all those living in the micro-social space suffer from such experiences and display worse health indicators as a result 28,29 . The message for health professionals is that women in situations of intimate partner violence may experience greater difficulties in maintaining regular care for themselves and their dependents, especially due to the greater visibility in the household's proximity.…”
Section: Discussionmentioning
confidence: 99%
“…As mudanças e fissuras nos sistemas de transmissão psíquica colocam em evidência a parte negativa da transmissão, o oculto, o não dito, permeando várias gerações. Estudos suge-rem que a violência é aprendida por meio da transmissão geracional (Barreto, Bucher-Maluschke, Almeida, & Souza, 2009), a partir da reprodução do modelo de educação recebido dos pais na infância, resultando numa perpetuação transgeracional do ciclo da violência. Há quem defenda que o não dito ou o segredo pode funcionar como estratégia inconsciente dos pais para preservar e proteger a vida psíquica de gerações seguintes (Salina, 2015).…”
Section: A Transmissão Geracionalunclassified